Producing the Greatest Good for Greatest Numbers-Implementation of Utilitarianism Principle: The Case Study of Producing Recombinant Protein of JDV - Endang Tri Margawati (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Advanced technology in molecular biology often uses microorganism, consequently, researcher should have a responsibility in producing of laboratory products safely both for human and their environment. This presentation was intended (1) to report recombinant protein research in the Jembrana Disease Virus (JDV); (2) to identify relevancy of the ethics towards the research of recombinant protein and (3) to discuss relationship of utilitarianism principle with the development of the recombinant protein. The Jembrana disease is an infectious virus caused by a virus classified as retrovirus of Retrovidae family. The disease only attacks Bali cattle (Bos javanicus) that caused about 20% mortality rate. Up to present, crude vaccine from lymph organ of acute infected Bali cattle is often used for vaccination. Development of the Jembrana vaccine was attempted to increase the availability of qualified Jembrana vaccine by recombinant DNA approaches subsequently could be used as vaccine substances. This article was presented with much bioethics issues in associated with recombinant protein research and other examples of related research which use micro-organism in their investigation. It is expected that bioethics could be a restrain for researchers who deal with advanced technology in their investigation.